The role of polymorphism (rs1800566) of NAD(F)H quinone oxidoreductase-1 in development of acute pancreatitis - T. A. Samgina; Y. V. Kanishchev; S. N. Grigor’Yev; P. M. Nazarenko; A. V. Polonikov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate the role of genetic polymorphism (rs1800566) of NAD(F)H quinone oxidoreductase-1 in development of acute pancreatitis in the Russian population. Material and methods. Whole blood samples were received from 349 unrelated AP patients and 329 unrelated individuals of Russian nationality having no gastrointestinal diseases. Mean age of patients was 48.9±13.1 years, mean age of healthy controls - 47.8±12.1 years. Genotyping of NQO1 gene polymorphism (rs1800566) was carried out by real-time polymerase chain reaction. Results. The association of polymorphism (rs1800566) of NQO1 gene T/T genotype with high risk of AP development, mostly - acute and non-biliary pancreatitis, in males. The risk of disease was elevated in patients with TT genotype irrespective of intensity and duration of alcohol intake, as well as in smoking patients with ST genotype at alcohol consumption exceeding 10 years, even in those receiving less than 199 g of ethanol per week.